Long‐term outcomes and management considerations after parathyroidectomy in the dialysis patient. Issue 6 (16th July 2019) - Kakani, Elijah; Sloan, David; Sawaya, B. Peter; El‐Husseini, Amr; Malluche, Hartmut H.; Rao, Madhumathi
Abstract: Parathyroidectomy (PTX) remains an important intervention for dialysis patients with poorly controlled secondary hyperparathyroidism (SHPT), though there are only retrospective and observational data that show a mortality benefit to this procedure. Potential consequences that we seek to avoid after PTX include persistent or recurrent hyperparathyroidism, and parathyroid insufficiency. There is considerable subjectivity in defining and diagnosing these conditions, given that we poorly understand the optimal PTH targets (particularly post PTX) needed to maintain bone and vascular health. While lowering PTH after PTX decreases bone turnover, long‐term changes in bone activity have been poorly explored. High turnover bone disease, usually present at the time a PTX is considered, often swings to a state of low turnover in the setting of sufficiently low PTH levels. It remains unclear if all low bone turnover equate with disease. However, such changes in bone turnover appear to predispose to vascular calcification, with positive calcium balance after PTX being a potential contributor. We know little of how the post‐PTX state resets calcium balance, how calcium and VDRA requirements change or what kind of adjustments are needed to avoid calcium loading. The current consensus cautions against excessive reduction of PTH although there is insufficient evidence‐based guidance regarding the management of chronic kidney disease ‐ mineral bone disease (CKD‐MBD) parameters in the post‐PTX state. This article aims to compile existing research, provide an overview of current practice with regard to PTX and post‐PTX chronic management. It highlights gaps and controversies and aims to re‐orient the focus to clinically relevant contemporary priorities in CKD‐MBD management after PTX.